Comparing the effectiveness of behavioral interventions in adults with co-occurring tobacco and substance use disorders: a systematic review of literature. Issue 1 (2nd January 2020) - Boatner, John; Rice, Timothy; Patterson, David; Thompson, Phyllis
ABSTRACT: This systematic literature review compares the eﬀectiveness of various behavioral interventions delivered to persons with co-occurring tobacco and substance use disorders. It examines ﬁndings of six randomized trials and three secondary analyses from randomized trials. Based on the ﬁndings of this literature review, support is given to the following: (1) The consequences of tobacco use and smoking are deadly, costly, and can have an inhibitory eﬀect on the progress of people in substance abuse treatment, (2) tobacco cessation options are a preventive intervention that can be easily incorporated into a treatment facility's standard of practice and should be made available within the context of all substance abuse treatment facilities, and (3) concurrently treating tobacco use disorder and substance use disorder(s) is an eﬀort that will help meet the social work profession's Grand Challenge to 'Close the Health Gap.'